Wreck the halls : a novel [large type] - Bailey, Tessa (Harper Large print, an imprint of HarperCollinsPublishers, 2023)
Stepping out of her comfort zone with her former best friend Beat Dawkins to convince their mothers to perform one last concert on Christmas Eve, Melody Gallard, the daughter of music royalty, discovers a decades-old scandal threatens to wreck everything--the reunion, their relationships with their mothers and their newfound love.